2005
DOI: 10.1139/h05-133
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Nitric Oxide and Oxidative Stress: Determinants of Endothelial Adaptations to Cardiovascular Disease and to Physical Activity

Abstract: Cardiovascular disease is the single leading cause of death and morbidity for Canadians. A universal feature of cardiovascular disease is dysfunction of the vascular endothelium, thus disrupting control of vasodilation, tissue perfusion, hemostasis, and thrombosis. Nitric oxide bioavailability, crucial for maintaining vascular endothelial health and function, depends on the processes controlling synthesis and destruction of nitric oxide as well as on the sensitivity of target tissue to nitric oxide. Evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 210 publications
(326 reference statements)
4
87
0
6
Order By: Relevance
“…Several reports have suggested that altered NO bioavailability contributes to altered vasomotion seen in hypertension 38,47,48 and NO is the primary dilator of large epicardial coronary arteries 3,6,49 as well as a mediator of flowinduced dilation in the coronary microcirculation. 2,5,6 Given the potential importance of the NO system in the etiology of hypertensive large artery disease, and given the fact that studies in other vascular beds have revealed a number of patterns of regulation of the NO system, the importance of which is not known in the coronary bed and in hypertension, it is important to bring attention to these factors as they may be important clinically and therapeutically.…”
Section: Introduction To Coronary Hemodynamics In Hypertensionmentioning
confidence: 99%
“…Several reports have suggested that altered NO bioavailability contributes to altered vasomotion seen in hypertension 38,47,48 and NO is the primary dilator of large epicardial coronary arteries 3,6,49 as well as a mediator of flowinduced dilation in the coronary microcirculation. 2,5,6 Given the potential importance of the NO system in the etiology of hypertensive large artery disease, and given the fact that studies in other vascular beds have revealed a number of patterns of regulation of the NO system, the importance of which is not known in the coronary bed and in hypertension, it is important to bring attention to these factors as they may be important clinically and therapeutically.…”
Section: Introduction To Coronary Hemodynamics In Hypertensionmentioning
confidence: 99%
“…Thus, when there is an increase in shear stress, the release of NO is accelerated. In coronary circulation, this stress force also has an important role in the adaptation of the coronary flow that can increase several times during the exercises 6,19,20 .…”
Section: Ghisi Et Al Physical Exercise and Endothelial Dysfunctionmentioning
confidence: 99%
“…Among the components involved in this coronary circulation improvement are: endothelial functionf. sm 9,20,57 ; the velocity of production and oxidation of NO 6,58 ; microcirculation 9,20,57,59 ; the regression of atherosclerotic lesions 3,60,61 ; the neoformation of collateral vessels 3,60,61 ; the decrease in blood viscosity 18 and the increase in the diastolic perfusion time 59 .…”
Section: Physical Exercise and The Vascular Endotheliummentioning
confidence: 99%
“…They show tissue antioxidant systems differ from each other in terms of capacity. High brain metabolic activity, oxygen consumption in excess tissues, such as liver and kidney, have a higher antioxidant capacity compared to other tissues (Fıçıcılar, Zergeroğlu, Tekin, & Ersöz, 2003;Rush, Denniss, & Graham, 2005).…”
Section: Introductionmentioning
confidence: 99%